Pengaruh Karakteristik Pemerintah Daerah Dan Opini Audit Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota Di Indonesia Tahun 2018) - Akhila Santika Kirana; Sulardi Sulardi (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2020)
This study aims to provide evidence of the effect of the local government characteristics and audit opinion on local government financial performance. Local government characteristics consist of local government’s size, capital expenditure, and independence rate. The sample was the regency/city government in Indonesia in 2018 that meets the criteria. The results of the analysis in 461 local governments showed an average efficiency of the local government's financial performance of 111.87%. The results of the analysis also showed local government size and capital expenditures affect positively on the local government's financial performance. Meanwhile, the independence rate did not affect the local government's financial performance, and the audit opinion showed significant negative influences on the local government's financial performance.